Peningkatan Prestasi Belajar Seni Rupa Materi Origami Melalui Model PjBL Berbantuan Media Papan Pola Alur - Rah Hajeng Listiawati; Okto Wijayanti (Varied Knowledge Journal, 2026)
The low academic achievement of students in visual arts serves as the practical problem underlying this research. Specifically in folding, cutting, and pasting skills in terms of both conceptual understanding and practical ability. The study aimed to examine the implementation of the Project-Based Learning (PjBL) model supported by "sequence pattern board" media in visual arts lessons focusing on origami, and to determine whether this approach could improve the academic achievement of Grade II-C students. A Classroom Action Research (CAR) methodology was employed, conducted over two cycles, with each cycle comprising two sessions. The research followed four stages: planning, implementation, observation, and reflection. Analysis of the results demonstrated an improvement in student achievement: the average score rose from 85.44 (with an 82% mastery rate, classified as good) in Cycle I to 89.85 (with a 97% mastery rate, classified as "excellent") in Cycle II. Success was measured using cognitive evaluation indicators ranging from C1 (recalling) to C4 (analyzing) and project skill assessment indicators, which included folding precision, accuracy in cutting along patterns, and proper pasting technique. The study concludes that implementing the Project-Based Learning (PjBL) model, supported by sequence pattern board media, is effective in enhancing the academic achievement of Grade II C students at SD Negeri 1 Sokanegara in visual arts lessons on origami.